APOIO MATRICIAL EM SAÚDE MENTAL NO MUNICÍPIO DE VITÓRIA/ES: OUTRAS POSSIBILIDADES DE PRODUÇÃO DE CUIDADO EM SAÚDE MENTAL - Duque, Pedro Henrique Cunha (2022)
The connection concerning mental health and primary medical care is not only relevant to caring, but also essential. Matrix based strategies, which aim to assure specialized support to health care teams and professionals, are paramount in mental care deba